Acclimation responses to temperature vary with vertical stratification: implications for vulnerability of soil‐dwelling species to extreme temperature events. (30th December 2012) - van Dooremalen, Coby; Berg, Matty P.; Ellers, Jacintha
Abstract The occurrence of summer heat waves is predicted to increase in amplitude and frequency in the near future, but the consequences of such extreme events are largely unknown, especially for belowground organisms. Soil organisms usually exhibit strong vertical stratification, resulting in more frequent exposure to extreme temperatures for surface‐dwelling species than for soil‐dwelling species. Therefore soil‐dwelling species are expected to have poor acclimation responses to cope with temperature changes. We used five species of surface‐dwelling and four species of soil‐dwelling Collembola that habituate different depths in the soil. We tested for differences in tolerance to extreme temperatures after acclimation to warm and cold conditions. We also tested for differences in acclimation of the underlying physiology by looking at changes in membrane lipid composition. Chill coma recovery time, heat knockdown time and fatty acid profiles were determined after 1 week of acclimation to either 5 or 20 °C. Our results showed that surface‐dwelling Collembola better maintained increased heat tolerance across acclimation temperatures, but no such response was found for cold tolerance. Concordantly, four of the five surface‐dwelling Collembola showed up to fourfold changes in relative abundance of fatty acids after 1 week of acclimation, whereas none of the soil‐dwelling species showed a significant adjustment in fatty acid composition. Strong physiological responses to temperature fluctuations may have become redundant in soil‐dwelling species due to the relative thermal stability of their subterranean habitat. Based on the results of the four species studied, we expect that unless soil‐dwelling species can temporarily retreat to avoid extreme temperatures, the predicted increase in heat waves under climatic change renders these soil‐dwelling species more vulnerable to extinction than species with better physiological capabilities. Being able to act under a larger thermal range is probably costly and could reduce maximum performance at the optimal temperature.